Voluntary agreements with industry - Mark Storey; Gale Allen Boyd; Jeffrey Dowd (Fondazione Eni Enrico Mattei (FEEM), 1997)
Voluntary Agreements (VAs) are becoming increasingly prominent in many countries as a policy instrument for achieving improvements in the environmental performance of industry. They aim to encourage industry led initiatives to set and meet environmental goals, to raise the environmental profile in corporate decision making, and to give participating industries the flexibility to achieve these goals in the manner which best meets their particular economic, social and political circumstances. The first section of this paper establishes an analytical framework for assessing the performance of VAs. This includes a classification of the different types of VAs and a discussion of the different criteria which could be used to evaluate their performance. The paper goes on to review the experience of several OECD countries with the implementation of VAs with energy intensive industries aimed at achieving improvements in energy efficiency or reducing the release of greenhouse gases. Three principle case studies are presented on Germany, the Netherlands and the United States with smaller studies on Canada and New Zealand. Each of the case studies sets out to describe the main characteristics of the VA, the different regulatory environments in which they are employed, and to evaluate their effectiveness in achieving environmental goals. Drawing on this information the paper goes on to identify several issues which need to be taken into consideration for the successful implementation of Vas. At present limited information is available to evaluate the success of VAs in different countries, especially in terms of economic efficiency and environmental effectiveness. This is partly because VAs have only been recently introduced in many countries and also because VAs rarely operate in isolation from other policy instruments. A significant part of this study, therefore, has focused on evaluation issues, such as how to compare performance of VAs against a "business as usual" baseline scenario or with historical trends. When such analysis has been used in this paper however, the difficulties and limitations of these methods are noted. VAs do, however, appear to play an important role in changing attitudes and awareness and generating and diffusing information. These so-called "soft effects" are difficult to quantify and often overlooked but appear to be one of the main advantages of a voluntary co-operative approach.
Keywords: 330; Umweltpolitik; Umweltmanagement; Selbstverpflichtung; Verhandlungen; Theorie